MECHANISMS FOR FORMING THE REGION'S BALANCED DEVELOPMENT STRATEGY IN THE CONDITIONS OF THE DIGITAL ECONOMY - Oltaev Sh.S, (TADQIQOTLAR, 2026)
Abstract: this article discusses the imbalances in the development of regional systems in the context of the digital economy. The development of mechanisms and tools  for  the  formation  of  a  balanced  socio-economic  development  strategy  of  the region is an urgent scientific task. Using a systematic approach, an enlarged diagram of the mechanism for the formation of a balanced development strategy of the region is developed and proposed. The sources of the formation of imbalances, priorities for the socio-economic development of the region, possible levers and tools for ensuring balanced  development,  and  directions  for  the  formation  of  scenarios  and  strategic alternatives  for  the  balanced  socio-economic  development  of  the  regions  are developed.